2012
DOI: 10.1007/s00011-011-0432-4
|View full text |Cite
|
Sign up to set email alerts
|

Histamine modulates salivary secretion and diminishes the progression of periodontal disease in rat experimental periodontitis

Abstract: Histamine is able to reduce periodontitis-induced damage to SMG and bone structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…The percentage of apoptotic cells in the salivary glands was enhanced in rats with ligature‐induced periodontitis as compared to that in the control rats (Nakamura‐Kiyama et al , ). Histamine reduces cell apoptosis (Deng et al , ), and accordingly, periodontitis‐induced increase in the proportion of apoptotic cells in rat submandibular gland (SMG) could be reduced by histamine treatment (Prestifilippo et al , ). Apoptosis in SMG might also be induced by depleted level of oxidative stress (OS) markers in the serum of patients with periodontitis (Ekuni et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…The percentage of apoptotic cells in the salivary glands was enhanced in rats with ligature‐induced periodontitis as compared to that in the control rats (Nakamura‐Kiyama et al , ). Histamine reduces cell apoptosis (Deng et al , ), and accordingly, periodontitis‐induced increase in the proportion of apoptotic cells in rat submandibular gland (SMG) could be reduced by histamine treatment (Prestifilippo et al , ). Apoptosis in SMG might also be induced by depleted level of oxidative stress (OS) markers in the serum of patients with periodontitis (Ekuni et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to highlight that previously reported data paradoxically showed similar improvements of periodontal disease employing subcutaneous histamine at low concentration (0.1 mg/kg), indicating that other histamine receptor subtype could also be involved in periodontal healthiness (Prestifilippo et al , ).…”
Section: Discussionmentioning
confidence: 84%
“…The evidence presented showed that 2 weeks of EP produced a considerable decrease in SMG salivary secretion, indicating that SMG functionality is severely altered and suggesting the development of anatomical and/or mechanistic alterations under this pathological condition. Accordingly, we previously reported that EP caused a marked reduction in the capacity of SMG to secrete saliva in response to cholinergic stimulation (Amer et al , ; Prestifilippo et al , ). The inhibitory effect on salivation induced by periodontitis was partially prevented by subcutaneously administered JNJ7777120 treatment.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations